Evaluating Community Welfare Effects of the Tourism Development on Geopark Caldera Toba - Tobing, Murniati; Afifuddin, Sya’ad; Ginting, Rahmanta; Sari, Raina Linda (Journal of Ecohumanism, 2024)
Tourism is one of the economic support systems that encourage economic growth in Indonesia. Indonesia as a country with good tourist attractions has enormous potential in creating jobs. The greater the employment opportunities, the lower the unemployment rate. The purpose of this study was to analyze whether tourism development has a positive and significant effect on economic activity to improve Community Welfare in the Lake Toba area. With variables consisting of 3 elements Variables consisting of indicators, namely: independent variables of tourism development (X) with indicators: policy (X1), institutions (X2), human resources (X3), facilities and infrastructure (X4), budget (X5), environment (X6), security (X7), social (X8), culture (X9), tourist attractions (X10), investment (X11), licensing (X12), promotion (X13), system (X14), tourists (X15). intervening variables/variables between economic impacts (Z) with indicators: economic growth (Z1), income (Z2), equity (Z3), poverty reduction (Z4), unemployment reduction (Z5). The dependent variable is community welfare (Y) with indicators: income equality (Y1), health (Y2), education (Y3), information (Y4), consumption expenditure (Y5). While the research method model used is the SmartPLS approach The number of samples is 351. Karo Regency, Simalungun Regency, North Tapanuli Regency, Pakpak Bharat Regency, Dairi Regency, Humbang Hasundutan Regency, Toba Regency, Samosir Regency. Economic impact has a positive but insignificant effect on community welfare. The results of the research on the analysis of the economic impact of integrated tourism development in the Lake Toba area on the welfare of the Lake Toba area community in North Sumatra Province can contribute to local government, central government, business people, tourists and the community. local government and central government can review policies or decisions that are less effective in increasing community income.